Pengaruh Etika Auditor dan Independensi Terhadap Kinerja Auditor di Kantor Akuntan Publik Jakarta - Haida Situmorang; Lorina Siregar Sudjiman (LP3M Universitas Putra Bangsa, 2022)
This study aims to determine the effect of the auditor's profession ethics and independency on auditor’s performance at public accountant Jakarta, either partially or simultaneously. This study uses primary data collacted of 77 respondents and using SPSS version 22 for analyzing the data. The results of the study prove that in partially based on result of the t test, auditor’s profession ethics has effect in evidence of t arithmetic > t table (3,209 > 1,99254) with significance value 0,002 < 0,05 and independency has effect in evidence of t arithmetic > t table (5,744 > 1,99254) with significance value 0,000 < 0,05. In simultaneosly based on result of the F test, auditor’s profession ethics and independency has effect on auditor performance at public accountant Jakarta in evidence of F arithmetic > F table (46,557 > 3,12) with significance 0,000 < 0,05 which is represented by 54,5 %.